Research on Improving the Financial Capacity of Farmers Based on Fuzzy Analytic Hierarchy Process - Gu, Yongyi; Xu, Kaijun; Hu, Xinyue; Chen, Mengting (Management Analytics and Social Insights, 2024)
This study uses the fuzzy analytic hierarchy process to deeply analyze the key factors that enhance the financial capabilities of farmers. The research results show that personal economic status is the dominant factor, with personal income, consumption, and savings becoming the core elements for enhancing financial capabilities. The importance of economic factors for the financial literacy of farmers is highlighted, providing a foundation for the formulation of targeted policies. Financial training and digital technology are also emphasized. The diversity of financial institutions is also seen as a key factor driving financial capabilities. Social factors have a relatively small impact on the research. Based on the comprehensive research results, it is proposed that the government should strengthen agricultural modernization, promote financial training and digital development, increase internet coverage, support diversified services of financial institutions, and encourage social capital investment to build a comprehensive policy framework to enhance the financial capabilities of farmers.